Sovereign and Equal, Unconditionally? The Principle of Sovereign Equality in International Law - Šmigová, Katarína (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
According to the principle of sovereign equality, a cornerstone of international law, all states hold equal legal status and rights irrespective of their status. However, in the context of international organisations, this principle might encounter practical limitations owing to structural hierarchies and power asymmetries. This chapter examines how sovereign equality applies within the United Nations (UN), and to a lesser extent, the European Union (EU). The analysis begins with a historical and theoretical exploration of sovereign equality, tracing its foundation in the Westphalian system and being verbalised legally within the UN framework. Particular attention is given to the Security Council’s veto power, emphasising the status of the UN Charter as an international treaty that has been adopted by all UN member states. Furthermore, the study explores the broader implications of globalisation and the relationship between states and international organisations, assessing how these developments reshape the relationship between these complementary international actors.